Removal of the unwinding provisions in the automated clearing settlement system: A risk assessment - Nicholas Labelle; Varya Taylor (Bank of Canada, 2014)
A default in the Automated Clearing Settlement System (ACSS) occurs when a Direct Clearer is unable to settle its final obligation. In August 2012, the Canadian Payments Association amended the ACSS by-law and rules to repeal the unwinding provisions from the ACSS default framework. Without unwinding, payment items are no longer returned by the defaulter to the other participants as a means of reducing the defaulter's final obligation. Instead, the other Direct Clearers (survivors) pay only additional settlement obligations to cover the defaulter's shortfall. To assess the potential exposures of an ACSS default without unwinding, we use simulations to estimate the value of additional settlement obligations for each survivor and compare these exposures to their capital and liquid assets. Results indicate that these exposures are indeed manageable by survivors and, therefore, that the ACSS does not pose systemic risk. – – Lorsqu'un adhérent au Système automatisé de compensation et de règlement (SACR) est dans l'incapacité de régler son obligation finale, il se trouve en situation de défaillance. En août 2012, l'Association canadienne des paiements a modifié les règles et les règlements relatifs au SACR dans le but d'abroger les dispositions de débouclement encadrant les défaillances du système. En absence de débouclement, le défaillant ne renvoie plus les effets de paiement aux autres adhérents pour réduire son obligation finale. Au lieu de cela, les autres adhérents (ou les survivants) s'acquittent simplement d'une obligation supplémentaire de règlement pour couvrir le déficit du défaillant. Pour évaluer les expositions potentielles à la défaillance d'un adhérent au SACR en absence de débouclement, les auteurs estiment par des simulations la valeur des obligations supplémentaires de règlement de l'ensemble des survivants et comparent ces expositions à leurs fonds propres et actifs liquides. Les résultats de l'étude indiquent que les survivants sont en mesure de gérer ces expositions et, par conséquent, que le SACR ne présente aucun risque systémique.
Keywords: C; C15; G; G01; G2; G3; 330; Payment clearing and settlement systems; Financial stability; Systèmes de compensation et de règlement des paiements; Stabilité financière